From Communications Game to Cities Tango. (1st January 2013) - Edmonds, Ernest; Franco, Francesca
The paper first discusses early work that predated internet art and that was concerned with active audience participation in electronic art and describes the path of development of the first author's artworks that have looked at human to human communication through electronic (computer) systems from 1970 until today. The fundamental concept has been to make artworks that explore human communication through conversations using restricted languages. The initial inspiration was a set of studies of early infant language development. The paper goes on to describe the latest developments in this series of artworks: Cities Tango.